Using Facebook and LinkedIn to Recruit Nurses for an Online Survey. (January 2019) - Stokes, Yehudis; Vandyk, Amanda; Squires, Janet; Jacob, Jean-Daniel; Gifford, Wendy
Social media is an emerging tool used by researchers; however, limited information is available on its use for participant recruitment specifically. The purpose of this article is to describe the use of Facebook and LinkedIn social media sites in the recruitment of nurses for an online survey, using a 5-week modified online Dillman approach. Within 3 weeks, we exceeded our target sample size ( n = 170) and within 5 weeks recruited 267 English-speaking nurses ( n = 172, Facebook; n = 95, LinkedIn). Advantages included speed of recruitment, cost-efficiency, snowballing effects, and accessibility of the researcher to potential participants. However, an analysis of the recruited participants revealed significant differences when comparing the sociodemographics of participants recruited through Facebook and LinkedIn, specifically relating to the characteristics of sex, age, and level of education. Differences between Facebook and LinkedIn as recruitment platforms should be considered when incorporating these strategies.